Climatic Fluctuations and the Diffusion of Agriculture - Ashraf, Quamrul; Michalopoulos, Stelios (The Review of Economics and Statistics, 2015)
This research examines the climatic origins of the diffusion of Neolithic agriculture across countries and archaeological sites. The theory suggests that a foraging society's history of climatic shocks shaped the timing of its adoption of farming. Specifically, as long as climatic disturbances did not lead to a collapse of the underlying resource base, the rate at which hunter-gatherers were climatically propelled to experiment with their habitats determined the accumulation of tacit knowledge complementary to farming. Consistent with the proposed hypothesis, the empirical investigation demonstrates that, conditional on biogeographic endowments, climatic volatility has a hump-shaped effect on the timing of the adoption of agriculture.